ROLE OF PARENT’S ATTRIBUTIONAL STYLE AND PARENT-CHILD RELATIONSHIP IN INCREASING SELF-ESTEEM OF CHILDREN WITH DYSLEXIA - Hilwa Abdullah @ Mohd. Nor; Diana Johan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Dyslexia is a specific learning disorder due to difficulties in phonological processing that impacts on the fluency and reading comprehension ability. The aim of this research is to identify the role of parents’ attributional style and parent-child relationship in determining the level of self-esteem in children with dyslexia. There are 24 respondents who consist of the parent or the caregiver of children with dyslexia along with the child were invited to participate in this research. The method used in this research is a cross-sectional study design using a quantitative approach. The researcher used three different tests to measure the variables involved. Tests used in this research consist of Causal Dimensional Scale II, Parent-Child Relationship Inventory and Rosenberg’s Self Esteem Scale. Results showed there is a significant relationship between parents’ attributional style and level of self-esteem in children with dyslexia. Attributional style measured in this research consists of four dimensions namely, locus of causality, external control, stability, and personal control. However, only two of the dimensions mentioned above are significantly related to the level of self-esteem in children with dyslexia. The two dimensions are external control (r = 0.408, p > 0.05) and personal control (r = 0.557, p > 0.05). Whereas, results showed there is no significant relationship between parent-child relationship and the level of self-esteem of children with dyslexia. In a nutshell, the role of parents’ attributional style in determining the level of self-esteem in children with dyslexia is notably significant while the relationship of parent-child does not influence the level of self-esteem in children with dyslexia.